Large-scale genome-wide association studies reveal the genetic causal etiology between ankylosing spondylitis and risk of leukemia and lymphocytic malignancies - Li, Guang; Dong, Changhu; Song, Yanping (Frontiers in Oncology, 2024)
BackgroundEvidence from multiple observational studies suggests that ankylosing spondylitis (AS) is associated with leukemia and lymphocytic malignancies. However, the obtained results are inconsistent, and the causal relationship still needs to be determined. In this context, we utilized two-sample Mendelian randomization (MR) to investigate potential causal associations between AS and leukemia and lymphocytic malignancies.MethodsThe analysis was conducted through published genome-wide association studies (GWAS). We obtained genetic data on AS as the exposure and leukemia, including lymphocytic leukemia, myeloid leukemia, and lymphocytic malignancies including lymphoma, multiple myeloma (MM) as the endpoint. The main method to evaluate causality in this analysis was the inverse variance weighting (IVW) technique. Additionally, we employed the weighted mode, weighted median, and MR-Egger regression for supplementary analyses. Finally, heterogeneity tests, sensitivity analyses, and multi-effect analyses are carried out.ResultsIn a random-effects IVW analysis, we found that genetic susceptibility to AS was associated with an increased risk of leukemia (OR = 1.002; 95%CI, 1.001–1.003; p = 0.003) and an increased risk of lymphocytic leukemia [OR = 1.001; 95% CI, (1.000–1.002), p = 0.008]. There was no evidence that AS was associated with lymphoma, myeloid leukemia, and MM.ConclusionOur research indicates that AS was associated with an elevated risk of leukemia, and further analysis of specific types of leukemia showed that the risk of lymphocytic leukemia was associated with AS. Our findings highlight the importance of active intervention and monitoring to mitigate leukemia, especially lymphocytic leukemia risk in patients with AS.